2022
DOI: 10.1021/acs.jafc.2c01621
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Branching Enzyme with a Novel Chain Transfer Mode Derived from Corallococcus sp. Strain EGB and Its Potential Applications

Abstract: Dietary starch with an increased content of resistant starch (RS) has the potential to reduce the prevalence of diabetes, obesity, and cardiovascular diseases. Here, an efficient glycogen branching enzyme, CcGBE, from Corallococcus sp. strain EGB was identified, and its relevant properties, including potential application in the preparation of modified starch, were evaluated. The purified CcGBE exhibited a maximal specific activity of approximately 20,000 U/mg using cassava starch as the optimal substrate. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A previous study found that the Corallococcus sp. strain was correlated with glucose metabolism in dietary starch and played an important regulatory role in the degradation of crude fiber in the body ( Ye et al., 2022 ). The cecum of rabbits is an important place for crude fiber digestion.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that the Corallococcus sp. strain was correlated with glucose metabolism in dietary starch and played an important regulatory role in the degradation of crude fiber in the body ( Ye et al., 2022 ). The cecum of rabbits is an important place for crude fiber digestion.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of recombinant plasmid pET‐29a (+)‐CcXyn was carried out using ClonExpress II One Step Cloning Kit (Vazyme Biotech Co. Ltd). The overexpression and purification of recombinant protein CcXyn were performed according to a previous report (Ye et al., 2022 ): E. coli BL21 (DE3) cells containing pET‐29a (+)‐CcXyn were cultured in Luria Bertani medium and induced with 0.2 mM isopropyl‐β‐ d ‐thiogalactopyranoside (Sigma‐Aldrich) at 16°C when OD 600 reached 0.5–0.6. The cells were harvested by centrifugation at 20,000 g and disrupted by sonication (Sonicator 201M) after suspending with 20 mM Tris–HCl buffer (pH 7.6).…”
Section: Methodsmentioning
confidence: 99%
“…were performed according to a previous report (Ye et al, 2022) as described previously (Laemmli, 1970).…”
Section: The Overexpression and Purification Of Recombinant Protein C...mentioning
confidence: 99%
“…A previous study found that the Corallococcus sp. strain was correlated with glucose metabolism in dietary starch and played an important regulatory role in the degradation of crude fiber in the body (Ye et al, 2022). The cecum of rabbits is an important place for crude fiber digestion.…”
Section: Discussionmentioning
confidence: 99%